2018
DOI: 10.1021/acsami.7b19349
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineered Safer Organic Battery through the Incorporation of Flame Retarding Organophosphonate Moiety

Abstract: Here, we report the first electrochemical assessment of organophosphonate-based compound as a safe electrode material for lithium-ion batteries, which highlights the reversible redox activity and inherent flame retarding property. Dinickel 1,4-benzenediphosphonate delivers a high reversible capacity of 585 mA h g with stable cycle performance. It expands the scope of organic batteries, which have been mainly dominated by the organic carbonyl family to date. The redox chemistry is elucidated by X-ray absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Complex versions of these compounds worthy of further discussion are metal–organic frameworks (MOFs). Very recently, MOFs have been the focus of extensive investigation as anode materials due to unique properties such as controlled pore size, redox activity, structural diversity, and well-established postprocess method. In analogy to transition metal oxides, the conversion reaction occurs in MOFs by inducing the reduction of transition metal and the formation of Li-containing organic species as final products. ,, In 2015, however, Lee et al discovered that further charge was passed after completion of the conversion reaction at nickel­(II) terephthalate (NiTP), delivering a high capacity of ∼1100 mAh g –1 . This value is remarkably higher than the theoretical capacity of ∼240 mAh g –1 based on an expected two-electron conversion reaction.…”
Section: Phenomena Proposed To Give Rise To Abnormal Reversible Capacitymentioning
confidence: 99%
“…Complex versions of these compounds worthy of further discussion are metal–organic frameworks (MOFs). Very recently, MOFs have been the focus of extensive investigation as anode materials due to unique properties such as controlled pore size, redox activity, structural diversity, and well-established postprocess method. In analogy to transition metal oxides, the conversion reaction occurs in MOFs by inducing the reduction of transition metal and the formation of Li-containing organic species as final products. ,, In 2015, however, Lee et al discovered that further charge was passed after completion of the conversion reaction at nickel­(II) terephthalate (NiTP), delivering a high capacity of ∼1100 mAh g –1 . This value is remarkably higher than the theoretical capacity of ∼240 mAh g –1 based on an expected two-electron conversion reaction.…”
Section: Phenomena Proposed To Give Rise To Abnormal Reversible Capacitymentioning
confidence: 99%
“…This approach intrinsically circumvents the dissolution penalty by adopting salt structures . In addition, several research groups have reported that binary metal–organic complexes can be applied as high-capacity electrode materials for lithium-ion or sodium-ion batteries, by co-utilizing transition-metal redox couples and redox-active organic ligands. , However, the role of nanosized metallic clusters embedded in an organic ligand matrix toward reversible electrochemical (de)­lithiation has remained unclear to date. Herein, we unravel the metal-dependent solid-state redox reversibility of coordination polymer frameworks through the comprehensive screening of the first-row transition-metal (3d-metal) cations and inverse-Würster-type molecules.…”
Section: Introductionmentioning
confidence: 99%